PENYIDIKAN TERHADAP TINDAK PIDANA PENELANTARAN ANAK OLEH KEPOLISIAN RESOR KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DI KOTA PEKANBARU - Haratua Manik, Buha Tumpak; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Protection of law to children can be interpreted as an effort to legal protection of the freedoms and rights of children as well as the various interests related to child welfare. In order to provide protection for children, the government has sought a policy that prohibit the crime of child. In the city of Pekanbaru cases of child neglect continue to rise because of the understanding of responsibility as parents has not been implemented correctly, plus children do not know about their rights protected by law. Though the act of making a waif clearly violated criminal provisions in child protection laws.The purpose of this skripsi, namely ; first, knowing the investigation process the crime of neglegct of children by police resort city of Pekanbaru by Law number 35 of 2014 on amandements to the Law number 23 of 2002 on the protection of children in the city of pekanbaru, second, barriers and what is being faced by investigators in the resort town of Pekanbaru police in the process of investigation of criminal neglect of children by Law number 35 of 2014 on amandements to the Law number 23 of 2002 on the protection of children in the city of pekanbaru. Types of classiefied research on sociological research which is interpreted is see the activities of the law being applicable by looking at the correlation between the law society, so as to reveal the effectiveness of the rule of law in society.Results of the discussion in this paper is; first, the process of investigation of criminal neglect of children in the city of Pekanbaru still continues to increase and not 100% effective, because in the case being a criminal neglect of children still part of the family members themselves, second, the obstacles faced in the investigation of criminal neglect of children among them, lack of witnesses and incompetence of witnesses to testify in the case, and the efforts made to overcome the obstacles in the process of investigation of criminal neglect of children is experts nor child psychologists and socialization or counseling about the importance of children for the future of the nation and it is all protected by legislation, family roles and coordination between government agencies.Keywords : Investigation, Neglected of Child.